Pregnant princess at the altar - Baine, Karin (Harlequin romance, 2023)
A red-carpet scandal...a shocking proposal! Princess Gaia cannot afford to bring further dishonor to her family--so she's keeping her pregnancy a secret! But when she meets movie star Niccolo at a premier, the frisson of attraction between them causes a scandal when they're caught in a compromising situation. With the incident splashed all over the headlines, Niccolo can't risk damaging his reputation any more. So he steps in to control the narrative...by announcing their royal engagement!